Litterfall deposition and leaf litter nutrient return in different locations at northeastern Mexico - González Rodríguez, Humberto; Domínguez Gómez, Tilo Gustavo; Cantú Silva, Israel; Gómez Meza, Marco Vinicio; Ramírez Lozano, Roque Gonzalo; Pando Moreno, Marisela; Fernández Navarro, Carlos Javier (Kluwer Academic Publishers, 2011)
The aim of this study was to determine the litterfall production and macronutrient (Ca, K, Mg, N, and P) deposition through leaf litter in four sites with different types of vegetation. Site one (Bosque Escuela) was located at 1600 m a.s.l. in a pine forest mixed with deciduous trees, second site (Crucitas at 550 m a.s.l.) in the ecotone of a Quercus spp. forest and the Tamaulipan thornscrub and third and fourth sites (Campus at 350 m a.s.l. and Cascajoso at 300 m a.s.l., respectively) were in the Tamaulipan thornscrub. Litter constituents (leaves, reproductive structures, twigs, and miscellaneous residues) were collected at 15-day intervals from December 21, 2006, throughout December 20, 2007. Collections were carried out in ten litter traps (1.0 × 1.0 m) randomly situated at each site of approximately 2,500 m2. Total annual litterfall deposition was 4407, 7397, 6304, and 6527 kg ha−1 y−1 for Bosque Escuela, Crucitas, Campus and Cascajoso, respectively. Of total annual litter production, leaves were higher varying from 74 (Bosque Escuela) to 86% (Cascajoso) followed by twigs from 4 (Cascajoso) to 14% (Crucitas), reproductive structures from 6 (Bosque Escuela) to 10% (Crucitas), and miscellaneous litterfall from <1 (Campus) to 12% (Bosque Escuela). The Ca annual deposition was significantly higher in Cascajoso (232.7 kg ha−1 y−1), followed by Campus (182.3), Crucitas (130.5) and Bosque Escuela (30.3). The K (37.5, 32.5, 24.8, 7.2, respectively), Mg (22.6, 17.7, 13.7, 4.5, respectively) followed the same pattern as Ca. However, N was higher in Campus (85.8) followed by Crucitas (85.1), Cascajoso (68.3), and Bosque Escuela (18.3). The P was higher in Campus and Crucitas (4.0) followed by Cascajoso (3.4) and Bosque Escuela (1.4). On an annual basis for all sites, the order of nutrient deposition through leaf litter was Ca > N> K > Mg > P, whereas on site basis of total nutrient deposition (Ca + N + K + Mg + P), the order was Cascajoso > Campus > Crucitas > Bosque Escuela. Ca, K, Mg, N, and P nutrient use efficiency values in leaf litter were higher in Bosque Escuela, while lower figures were acquired in Cascajoso and Crucitas sites. It seems that the highest litterfall deposition was found in the ecotone of a Quercus spp. forest and the Tamaulipan thornscrub; however, the Tamaulipan thornscrub vegetation alone had better leaf litter nutrient return.